Harmonising Worship and Noise: Community Responses to Loudspeaker Regulations in Bali and Manado - Bukido, Rosdalina; Gunawan, Edi; Makka, Misbahul Munir (UIN Sunan Gunung Djati Bandung, 2024)
In multicultural societies, the regulation of worship loudspeakers, particularly those affecting the Muslim community, has sparked significant debate, ranging from strong support to outright rejection. This study seeks to explore the social tensions arising from these regulations, focusing on the culturally diverse regions of Bali and Manado. Employing a qualitative approach, interviews were conducted with religious leaders, community figures, and local government officials to gain insight into the community's reactions. The findings reveal two predominant responses. On one hand, some view the regulations as unnecessary, believing that the established tradition of tolerance has allowed diverse religious practices to coexist peacefully without significant issues related to loudspeakers. On the other hand, others feel that the loudspeaker use is excessive, disturbing their rest and seeking quieter times. Some members of the Muslim community perceive the regulation as discriminatory, noting that other religious groups might also use loudspeakers at higher volumes. This study offers valuable insights for policymakers on how regulatory interventions can influence social harmony in diverse environments, highlighting the importance of adjusting regulations to respect religious diversity and equitably manage public auditory spaces.